Salmonellosis in the Republic of Georgia: Using Molecular Typing to Identify the Outbreak-Causing Strain - Alexander Sulakvelidze (Emerging Infectious Diseases, 2000)
In May 1998, three large outbreaks of salmonellosis, affecting 91 persons, were identified in the Republic of Georgia. Eighteen Salmonella Typhimurium strains were characterized by arbitrary primed polymerase chain reaction and pulsed-field gel electrophoresis; the results suggested that all cases were part of a single outbreak caused by a distinct clonal strain.